2020
DOI: 10.1007/s13318-020-00622-8
|View full text |Cite
|
Sign up to set email alerts
|

Elution Profiles of Synthetic CaSO4 Hemihydrate Beads Loaded with Vancomycin and Tobramycin

Abstract: Backgrounds and Objectives The use of local antibiotic delivery vehicles is common in the management of biofilm-related infections as they provide high concentrations of local antibiotics while simultaneously avoiding complications from systemic toxicity. We present a 100% pure synthetic calcium sulfate hemi-hydrate mixed with 240 mg tobramycin and 500 mg vancomycin per 10 cc mixture for use in revision surgeries of periprosthetic joint infections (PJIs). The purified carrier demonstrates bioabsorbablity, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Using the Center for Biofilm Engineering (CBE) drip reactor, the calcium sulfate antibiotic loaded hemihydrate pellets destroyed all biofilm that was surface exposed [ 13 ]. A calcium sulfate pellet was beneficial in our implementation of a one-stage procedure because it was bio-absorbable, demonstrated osteoconductive potential, eliminated dead space, and delivered high concentrations of antibiotics locally without adverse systemic toxicity [ 26 ]. Compared to other variants, the carrier used was hydrophilic, possessed a physiologic pH, and was synthetically pure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Center for Biofilm Engineering (CBE) drip reactor, the calcium sulfate antibiotic loaded hemihydrate pellets destroyed all biofilm that was surface exposed [ 13 ]. A calcium sulfate pellet was beneficial in our implementation of a one-stage procedure because it was bio-absorbable, demonstrated osteoconductive potential, eliminated dead space, and delivered high concentrations of antibiotics locally without adverse systemic toxicity [ 26 ]. Compared to other variants, the carrier used was hydrophilic, possessed a physiologic pH, and was synthetically pure.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the CRISPR/Cas system allows the bacteria’s immune system to recognize and destroy the foreign viral genetic material in a highly adaptable and heritable mechanism [ 19 ]. It takes to kill bacterial biofilm log 3 above the minimum inhibitory concentration (MIC) to kill the biofilm with systemic antibiotics [ 13 , 26 ]. Biofilm with systemic antibiotics kills the outer cells, but the inner, low metabolic cells persist (persister cells) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak identified exactly at 1619 cm -1 alludes to the flexion vibrations of water molecules present in the sample. Finally, it was found that the peaks located in the wave range between 1100 and 590 cm -1 are attributed to the asymmetric vibrations of the bonds of the sulfate group -SO 4 2- (Huynh et al 2020;Maale et al 2020;Zhang et al 2020).…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 98%
“…The use of CS as a material for management of residual dead space offers important advantages as it is resorbed in vivo [ 11 , 12 ] and does not require subsequent surgical removal. CS can also be combined with antibiotics to treat infections [ 13 ].…”
Section: Introductionmentioning
confidence: 99%